Igneous Rock Associations 8. Arc Magmatism II:: Geochemical and Isotopic Characteristics - Murphy, J. (Geoscience Canada, 2007)
Geochemical and isotopic data provide insights into the origin and evolution of magmatism found at destructive plate margins. Tholeiitic magmas are dominant in the early stages of oceanic island-arc genesis and calc-alkalic magmas are most common in mature oceanic arcs and in continental arcs where they may range from basalt to rhyolite in composition, including voluminous intermediate (andesitic) rocks. Experiments suggest that calcalkalic mafic magmas are formed by melting of a hydrated mantle wedge and undergo low pressure fractional crystallization under near-H2O saturated conditions. Intermediate to felsic magmas are derived in a wide variety of ways, including the fractionation of a more mafic parent, mixing between mafic and felsic magmas (a process supported, in many cases, by field and textural evidence), crustal contamination, or partial melting of the crust. All these processes appear to take place, to some degree, in arc systems, although in any given arc system, one mechanism may predominate. Arc-related calc-alkalic and tholeiitic basalts typically show moderate degrees of light rare-earth-element (LREE) enrichment, and flat heavy rare-earth-element (HREE) profiles, indicating an origin in a shallow (spinel lherzolite) mantle. More evolved magmas exhibit Eu anomalies, consistent with low pressure plagioclase fractionation. Compared to within-plate settings, tholeiitic and calc-alkalic arc magmas have lower abundances in high-field-strength (HFS) elements, possibly because these elements are bound during the accessory phases in the mantle wedge, and are stable during partial melting. Compared to arc tholeiites, calc-alkalic magmas have higher abundances of incompatible large ion lithophile (LIL) elements reflecting enrichment in the mantle wedge source. This characteristic depletion in HFS, and enrichment in LIL, elements, in arc magmas is the basis for a variety of discrimination diagrams. These diagrams constrain processes operating in modern and ancient arc systems and include chondrite-normalized, MORB-normalized and mantle-normalized spidergrams, which are characterized by jagged patterns of trace-element abundances (in contrast to the relatively smooth patterns of within-plate suites). Some arc suites have depleted initial 143Nd/144Nd and lower initial 87Sr/86Sr than the bulk earth, and are similar to MORB. Other suites have enriched isotopic patterns consistent with the influence of subducted oceanic sediments on the composition of the magma. Samarium-Nd and Rb-Sr isotopic studies can be used to distinguish between felsic magmas derived from fractional crystallization of a more mafic parent (which would have similar values) and those derived from the melting of ancient crust.